O papel do psicopedagogo no ensino fundamental 1 - Derballe, Rafaella Lopes Sanchez (2012)
This monograph aimed to seek an understanding of the role of psychopedagogists in the school context, more precisely on Elementary Education 1. A bibliographic survey was conducted on the historical, the main features of the psychopedagogy as area of knowledge ( key moments of its construction; different ways of thinking about their subject; different articulations inter theoretical that underpin theoretical constructions and the psychopedagogic work of Argentines an Brazilians psychopedagogists) and the main features of psychopedagogy as area of intervention ( different types of performance, the intervention context, the objectives pursued, of activities, and own procedure developed. The National Curriculum Parameters and the Curriculum Orientations related to Elementary Education 1, were also explained and related to the goals and worries of psychopedagogic work. Lastly, reflected on a concrete situation – the complain of a school in relation to a child – experienced by author during the realization of the regular stage, provided by the Pedagogy course in order to clarify the understanding gained on the role of psychopedagogists in the school context